2019
DOI: 10.1152/ajprenal.00040.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sustained, delayed, and small increments in glomerular permeability to macromolecules during systemic ET-1 infusion mediated via the ETA receptor

Abstract: Emerging evidence indicates that endogenous production of endothelin (ET)-1, a 21-amino acid peptide vasoconstrictor, plays an important role in proteinuric kidney disease. Previous studies in rats have shown that chronic administration of ET-1 leads to increased glomerular albumin leakage. The underlying mechanisms are, however, currently not known. Here, we used size-exclusion chromatography to measure glomerular sieving coefficients for neutral FITC-Ficoll (molecular Stokes-Einstein radius: 15–80 Å, molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…415 In a model of salt-sensitive hypertension, Sorokin and associates 416 have recently found that ET-1 contributes to contraction of afferent arterioles in the kidney via p66Shc and that deletion of the src homology-2 (SH2) domain-containing adaptor protein p66Shc in part protects from hypertension-associated renal injury, identifying a novel, ET-1-dependent mechanism that propagates glomerulosclerosis through microvascular constriction. Chronic, deleterious effects of ET-1 in kidney diseases are mediated primarily through the ET A receptor, 414,417 which also mediates acute effects on the glomerular filtration barrier which are maintained by podocytes 31,418 : Dolinina et al 419 found that acute infusion of ET-1 induces rapid changes in glomerular permeability to macromolecules, an effect that was abrogated by concomitant infusion of an ET A -selective antagonist, indicating that excess ET-1 concentrations can rapidly worsen glomerular permeability which is likely important for critical care settings, such as acute renal failure, myocardial infarction with heart failure, or sepsis. Similar to patients with CAD, 250,265 in patients with chronic renal disease, ET-1 may have effects that go beyond the kidney: Farrah et al 420 found that chronic ET A -receptor blockade reduced circulating levels of LDL (low-density lipoprotein)-cholesterol, lipoprotein (a) (Lp(a)) and PCSK9 (proprotein convertase subtilisin/ kexin type 9) while increasing HDL (high-density lipoprotein) cholesterol, resulting in an overall improvement of the cardiovascular risk profile.…”
Section: Renal Disease Chronic Proteinuric Renal Diseasementioning
confidence: 99%
“…415 In a model of salt-sensitive hypertension, Sorokin and associates 416 have recently found that ET-1 contributes to contraction of afferent arterioles in the kidney via p66Shc and that deletion of the src homology-2 (SH2) domain-containing adaptor protein p66Shc in part protects from hypertension-associated renal injury, identifying a novel, ET-1-dependent mechanism that propagates glomerulosclerosis through microvascular constriction. Chronic, deleterious effects of ET-1 in kidney diseases are mediated primarily through the ET A receptor, 414,417 which also mediates acute effects on the glomerular filtration barrier which are maintained by podocytes 31,418 : Dolinina et al 419 found that acute infusion of ET-1 induces rapid changes in glomerular permeability to macromolecules, an effect that was abrogated by concomitant infusion of an ET A -selective antagonist, indicating that excess ET-1 concentrations can rapidly worsen glomerular permeability which is likely important for critical care settings, such as acute renal failure, myocardial infarction with heart failure, or sepsis. Similar to patients with CAD, 250,265 in patients with chronic renal disease, ET-1 may have effects that go beyond the kidney: Farrah et al 420 found that chronic ET A -receptor blockade reduced circulating levels of LDL (low-density lipoprotein)-cholesterol, lipoprotein (a) (Lp(a)) and PCSK9 (proprotein convertase subtilisin/ kexin type 9) while increasing HDL (high-density lipoprotein) cholesterol, resulting in an overall improvement of the cardiovascular risk profile.…”
Section: Renal Disease Chronic Proteinuric Renal Diseasementioning
confidence: 99%
“…In rats, infusion of ET-1 induced a prolonged state of glomerular large-pore hyperpermeability. ET A , but not ET B, blockade reversed the state of glomerular hyperpermeability [5]. Thus, glomerular leakage of plasma proteins could be due, at least in part, to increased local ET-1 activity.…”
Section: General Pathobiology Of Endothelin and The Kidneymentioning
confidence: 87%
“…Glomerular hyperpermeability can be induced by a number of pharmacological and experimental challenges (Axelsson et al, 2012;Dolinina et al, ,2016Dolinina et al, , , 2018Dolinina et al, , , 2019 often being of a transient nature such that the permeability approaches baseline levels after the injurious stimuli are removed. While proteinuria is often associated with structural alterations in the renal filter, such reversible alterations imply that the structural changes occurring in the GFB are of a brief and non-persistent nature.…”
Section: Discussionmentioning
confidence: 99%